Gasless endoscopic thyroidectomy via modified areola approach with a simple flap-lifting technique - Guo, Tao; Wu, Zehui; He, Juntong; Liu, Defeng; Wan, Hong; Li, Yangyang; Peng, Shihao; Xu, Aman (Frontiers in Endocrinology, 2022)
Objective: Studies have shown that carbon dioxide (CO2) insufflation during endoscopic thyroidectomy is associated with many risks. Recently, we have designed a simple lifting tool using Kirschner wire. We aimed to use this tool for flap-lifting in modified areola approach endoscopic thyroidectomy and compare it with conventional CO2 insufflation. Methods: In a prospective study, patients who underwent endoscopic thyroidectomy via modified areola approach were randomly assigned in to gasless (n = 20) or CO2 groups (n = 22). Pre-operative variables included age, gender, tumor diameter, and clinical diagnosis. Intra-operative hemodynamic monitoring included mean arterial pressure, heart rate, pulse oximetry, end-tidal carbon dioxide (ET-CO2) and arterial pH. Other intra-operative details included total operative time, operative blood loss, conversion from endoscopic surgery to open surgery, intra-operative events, and endoscope video score. Postoperatively, the hospital stay, drainage volume, and complications were recoded. Results: Patient characteristics were not different between the two groups. During the operation, ET-CO2 levels were significantly higher in the CO2 group (P < 0.05), whereas arterial pH levels were significantly lower (P < 0.05). The CO2 group had longer operation time and higher endoscope clarity VAS score than gasless group. Hospital stay, drainage volume, and postoperative complications did not differ significantly between the two groups (P > 0.05). Conclusions: The gasless endoscopic thyroidectomy we performed via our Kirschner wire hook was safe, feasible, and yielded good results.